Revitalizing Regional Languages Through Storytelling and Read-Aloud Activities at Elementary School Level in Bangka - Atik Rahmaniyar; Eva Harista; Fazrul Sandi Purnomo (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe and explain the process of revitalizing regional languages ​​and analyze the results of implementing these activities through read-aloud activities, especially at the elementary school level in Bangka. This research is motivated by the phenomenon of the threat of regional language extinction in daily activities. Regional languages ​​are one of the cultural identities that are characteristic of a region. The active role of a community's culture is directly proportional to the enthusiasm and pride of the community in using their regional language. The method used in this study is descriptive qualitative conducted naturally on natural objects. Data were collected through participatory observation, in-depth interviews with teachers, questionnaires with students, and documentation of classroom activities. This study obtained findings in the form of an overview and process of implementing storytelling through the read-aloud method using children's storybooks in the Bangka regional language. Data analysis shows that the read-aloud method functions as an introduction in the cognitive process that makes it easier for students to understand regional languages. Based on this explanation, it can be concluded that revitalizing regional languages ​​through read-aloud storytelling activities is effective in rekindling interest in the habit of daily conversation in formal and non-formal settings using regional languages. Furthermore, it is recommended that schools integrate this research method into the local content curriculum which will have an impact as a solution so that regional languages ​​in formal and non-formal environments do not experience the phenomenon of extinction.